LEVEL OF EDUCATION AND EMPLOYMENT IN PUNJAB (International Journal of Food and Nutritional Sciences, 2022)
Punjab, which holds the status of the most prosperous state in India, has been going backward for the last one and a half decades. The labor force of Punjab is also shifting from agriculture sector to non-agriculture sector. The sectoral shift from agriculture to non-agriculture requires that the labor force be more educated and skilled. So in the context of the above discussion, we analyze the state of education in Punjab on the basis of literacy rate and level of education. Labor participation rate and educational level of workers are looked at to see the level of employment. The Punjab government has also evaluated the expenditure on education in the annual plans. Education and manpower planning should become an important issue of the state government. The government should adopt its strong policy on education and employment and not shrink the organized sector but expand it to make this state a leader again.